Analisis Semiotika Representasi Women Support Women dalam Film Qorin - Rio Putra Pratama (Institut Nalanda, 2023)
Films with magical, astro or mystical nuances are the genre or feel of films that are most liked by Indonesian people, who are known as a religious and magical society. One film that combines the religious and magical cultural background of Indonesian society is the film Qorin . This research aims to analyze the spirit and movement of women supporting women implied in the film Qorin . This research uses the Semiotics theory coined by Charles Sanders Pierce combined with descriptive qualitative research methodology. This method is used to analyze scenes in the film Qorin which depict women supporting women through the symbols shown. These symbols represent the existence of unequal power relations between women and men, such as female students who do not have the power to refuse orders from their ustadz, and wives who are unable to give advice to their husbands. However, besides that, there is a symbol that shows the great strength of the female characters in the film if they support each other.